Фонетичні маркери книжності в мові Пантелеймона Куліша - Кумеда, О. (Культура слова, 2021)
Пропоноване спостереження здійснено переважно на матеріалі першодруків творів Пантелеймона Куліша і є частиною цілісного дослідження мови письменника на тлі рідного
йому східнополіського говору північного наріччя. У статті
розглянуто окремі риси мови Куліша у світлі їхнього зв’язку
з давнішою книжною традицією української літературної
мови. Зокрема, з урахуванням свідчень діалектних джерел, писемних пам’яток, а також тогочасної мовно-літературної
практики проаналізовано збереження *о в окремих словоформах; з’ясовано, що, попри безперечний вплив на мову П. Куліша
питомого говіркового довкілля, розглянуті елементи фонетики відбивають насамперед усталений за часів автора мовно-літературний стандарт східноукраїнської редакції і водночас
оприявнюють тяглість попередньої книжної традиції, опертої на північні говори; звернуто увагу на стилістичні функції
фонетичних маркерів книжності в мові П. Куліша. In the works about P.A. Kulish’s language and his role in the
history of the Ukrainian literary language there is no deep and
profound analysis of the writer’s idiolect formation. The proposed
observation is part of a holistic study that is devoted to study of
P. A. Kulish’s language due to the аestern Polissya dialect; the
work is based on the primary sources (the texts published during
the author’s life), where their phonetic, morphological and lexical
characteristics are considered. In this work the experience of the
researchers of T. G. Shevchenko’s language is taken into account.
But it is stressed that the methodology of studying the writer’s
idiolect used in the thesis was improved, that is connected with the
increasing basic empirical foundation (the maps of the Ukrainian
Language Atlas, dialectal speech recordings, personal observations).
As a result, it was found that the language of P. Kulish’s first editions
is generally characterized by the variability of the realization of
*o in the closed syllable of multi-syllable word forms, which is
justified by the dialectal basis of the writer’s language.
The article considers the implementation of *о in the Kulish’s
language in connection with the ancient bookish tradition of the
Ukrainian literary language. In particular, taking into account
the evidence of dialectal sources, written monuments, as well as
the linguistic and literary practice during the life of Kulish, the
preservation of *o in some word forms is analyzed; it was found
that, despite the undeniable influence on the language of P. Kulish
specific speech environment, the considered elements of phonetics
primarily reflect the established in the time of the author linguistic
and literary standard of the East Ukrainian edition and at the
same time show the longevity of the previous bookish tradition
(безголов’є); attention is paid to the stylistic functions of phonetic
markers of bookish tradition in the Kulish’s language (кості,
покойний, заупокойний). In this context, the subject of analysis
also became lexical archaisms with *o (гетьманський cтолець,
церковні / апостольські стольці), which are reflected in the texts
of various genres in order to express a specific historical epoch.
Among the historicisms with *o recorded Запорожжя, Мосток
мертвецький and others.